The Impact of Goal-Setting Training on Enhancing Self-Efficacy in the Dayak Entrepreneurial Community - Sulistyani, Nuraida Wahyu; Ramadhan, Yoga Achmad (Journal of Educational, Health and Community Psychology, 2025)
Entrepreneurship is a vital component of economic development, especially within ethnic communities that possess distinct cultural and social strengths. A significant challenge facing the entrepreneurial community of the Dayak tribe in Kalimantan is low self-efficacy, which refers to individuals' confidence in their ability to confront challenges and accomplish goals. This lack of confidence creates barriers to business development. This study aims to examine the impact of goal-setting training on improving the self-efficacy of Dayak entrepreneurs. The subjects of this study were 40 Dayak entrepreneurs, divided into 20 subjects in the experimental group and 20 in the control group. Data were collected using a self-efficacy scale developed by Sulistyani et al. (2022), interviews, focus group discussions, and observations. The research design employed was a pre-post control group design. The analysis was conducted using both quantitative and qualitative methods. Quantitative analysis utilized Repeated Measures ANOVA to assess self-efficacy levels among Dayak entrepreneurs following the goal-setting training. Qualitative analysis was based on observations, interviews, focus group discussions, and worksheets. The findings indicated an increase in self-efficacy scores across pre-test, post-test, and follow-up measurements, with a Mean Square value of 487.675, F = 37.205, and p = 0.000 (p < 0.05). This demonstrates an interaction between measurements (pre-test, post-test, and follow-up) and groups (experimental and control). The interaction highlights a significantly different increase in scores across the measurements between the two groups. The conclusion of this study is that goal-setting training can enhance the self-efficacy of Dayak entrepreneurs. These findings contribute significantly to the development of more effective training strategies for the Dayak community and provide a foundation for implementing goal-setting-based training programs in other ethnic communities facing similar challenges.